2017
DOI: 10.1108/ijoem-03-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Active trading and retail investors in Malaysia

Abstract: Purpose -The purpose of this paper is to investigate who trade actively in the Malaysian stock market and what determines investors' active trading decisions. Design/methodology/approach -Using a cross-sectional survey on individual investors, the study identifies active and inactive investors and then, investigates active trading by estimating binary logistic regression. Findings -Active investors in Malaysia are more likely to be male, working in non-finance-related sectors and are more experienced. The like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Traditional financial studies have approached this subject differently by highlighting the economic viewpoints that assume an individual as a rational decision-maker to the best course of action (Schiffman and Kanuk, 2007). It also supports the buy-and-hold trading strategy which is considered as an optimal and a generally accepted benchmark (Khan et al , 2017) to justify investors' rational and persistent behaviour. However, schools of new thoughts such as bounded rationality (Simon, 1955), cognitive dissonance (Hardyck et al , 1965), prospect theory (Kahneman and Tversky, 1979) and heuristics (Tversky and Kahneman, 1974) and so on have shown that these hypotheses are inconsistent and not able to explain why investors behave in such an unpredictive way.…”
Section: Introductionsupporting
confidence: 55%
“…Traditional financial studies have approached this subject differently by highlighting the economic viewpoints that assume an individual as a rational decision-maker to the best course of action (Schiffman and Kanuk, 2007). It also supports the buy-and-hold trading strategy which is considered as an optimal and a generally accepted benchmark (Khan et al , 2017) to justify investors' rational and persistent behaviour. However, schools of new thoughts such as bounded rationality (Simon, 1955), cognitive dissonance (Hardyck et al , 1965), prospect theory (Kahneman and Tversky, 1979) and heuristics (Tversky and Kahneman, 1974) and so on have shown that these hypotheses are inconsistent and not able to explain why investors behave in such an unpredictive way.…”
Section: Introductionsupporting
confidence: 55%
“…Information related to macroeconomic variables may predict the variation in trading decisions. The significance of macroeconomic expectations in decision-making has been echoed in financial literature [8]. According to the consumptionbased capital asset pricing model and other models, it was admitted that stock market participation could be much lower than predicted [9].…”
Section: Literature Review 21 Theoretical Foundationmentioning
confidence: 99%
“…This study adopted 5 items from Akhtar and Das [29]. For the measurement of stock market participation, this study adopted 5 items from Khan, Tan, and Chong [8] and Akhtar and Das [29]. All items adapted in this study presented in Appendix A.…”
Section: Measures Of Constructsmentioning
confidence: 99%
“…Traditional finance research studies have taken a different approach to this topic, emphasizing economic opinions that presuppose an individual to be a rational decisionmaker (Schiffman and Kanuk, 2007) when it comes to the optimum course of action. It also endorses the purchase trading policy, which is widely regarded as an optimal and widely accepted benchmark for supporting investors' logical and consistent behavior (Khan et al, 2017). Though, researcher like Simon (1955) (bounded rationality), Kahneman and Tversky (1979) (prospect theory), Hardyck et al (1965) (cognitive dissonance) and Tversky and Kahneman (1974) (heuristics) shown that the hypotheses of traditional finance are unpredictable and not able to enlighten why individual act in such an inconsistent way.…”
Section: Introductionmentioning
confidence: 96%